2010
DOI: 10.1016/j.bbamem.2009.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Membrane charge dependent states of the β-amyloid fragment Aβ (16–35) with differently charged micelle aggregates

Abstract: Abeta (16-35) is the hydrophobic central core of beta-amyloid peptide, the main component of plaques found in the brain tissue of Alzheimer's disease patients. Depending on the conditions present, beta-amyloid peptides undergo a conformational transition from random coil or alpha-helical monomers, to highly toxic beta-sheet oligomers and aggregate fibrils. The behavior of beta-amyloid peptide at plasma membrane level has been extensively investigated, and membrane charge has been proved to be a key factor modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 86 publications
9
23
0
Order By: Relevance
“…The ratios of the integrated bands associated with the H‐bonded vs free NH groups point clearly to almost fully developed (≥ 90%) 3 10 ‐helical structures for all peptides examined . These findings are in full agreement with the spectroscopic and X‐ray diffraction literature data of peptides rich in the known helicogenic TOAC and Aib residues in CDCl 3 solution and in the crystal state.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The ratios of the integrated bands associated with the H‐bonded vs free NH groups point clearly to almost fully developed (≥ 90%) 3 10 ‐helical structures for all peptides examined . These findings are in full agreement with the spectroscopic and X‐ray diffraction literature data of peptides rich in the known helicogenic TOAC and Aib residues in CDCl 3 solution and in the crystal state.…”
Section: Resultssupporting
confidence: 87%
“…More specifically, we analyze a series of peptides consisting of stretches of the non‐coded, host α‐amino acid α‐aminoisobutyric acid (Aib), combined with one or two 4‐amino‐1‐oxyl‐2,2,6,6‐tetramethylpiperidine‐4‐carboxylic acid (TOAC) guest residues. Both TOAC and Aib are known to strongly stabilize regular 3 10 ‐helices . The backbone and side‐chain conformations of TOAC are remarkably constrained, providing well‐defined distances between the stable nitroxide free radicals of two TOAC residues.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies concerning amyloidogenesis point to the special role of hydrophobic residues [55][56][57]. If interactions between residues forming the sequence do not promote the formation of a common, central hydrophobic core, a different type of ordering may take hold-one in which local peaks and troughs aggregate linearly.…”
Section: Discussionmentioning
confidence: 99%
“…In such a model, cell membranes appear to act as two-dimensional aggregation templates. For example, complementary CD, NMR, and electron paramagnetic resonance analyses (Grimaldi et al, 2010) performed in SDS and DPC (dodecyl phosphocholine) micelles showed that A␤ 16 -35 undergoes a conformational transition from a soluble helical structure, to a U-turn-shaped conformation, and fluorescence and CD spectra at varied temperatures (Yoda et al, 2008) show that the flat surface of tightly packed PC (phosphatidylcholine) membranes (a major component of neuronal cell membranes) appears to serve as a platform for nonelectrostatic interactions and self-association. Furthermore, at near-physiological concentrations of A␤ only the small oligomeric A␤ species of ϳ46 Å are relevant, they are capable of attaching to the PC12 cell membrane, and they assemble in situ to form much larger complexes (Nag et al, 2010).…”
Section: Discussionmentioning
confidence: 99%